2021
DOI: 10.9734/ijpss/2021/v33i130416
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Soil Moisture Reading Obtained with Soil Moisture Sensors and Gravimetric Method for Scheduling of Irrigation in Maize

Abstract: A field experiment was conducted at Water Technology Centre farm (WTC), College of Agriculture, Rajendranagar, Hyderabad for studying the correlation between the soil moisture reading obtained with soil moisture sensors and gravimetric method. The experiment was designed in split plot with two main treatments comprising of surface furrow (M1) and drip irrigation (M2) methods and six irrigation schedules were assigned to sub treatments and replicated thrice. Significantly higher grain yield (7.05 t ha-1) of mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Irrigation scheduled based on nano sensors in maize recorded highest plant height, highest dry matter production over other sensors under drip irrigation method [13]. "Soil moisture sensorbased drip irrigation on sugarcane at different fertilizer levels and reported that the combination of 125 per cent Etc along with 100 per cent RDF as WSF recorded higher cane yield of while Drip irrigation at 75 per cent Etc along with fertigation of 100 per cent RDF as WSF recorded highest WUE" [14].…”
Section: Nano Sensor With Drip In Crop Productionmentioning
confidence: 98%
“…Irrigation scheduled based on nano sensors in maize recorded highest plant height, highest dry matter production over other sensors under drip irrigation method [13]. "Soil moisture sensorbased drip irrigation on sugarcane at different fertilizer levels and reported that the combination of 125 per cent Etc along with 100 per cent RDF as WSF recorded higher cane yield of while Drip irrigation at 75 per cent Etc along with fertigation of 100 per cent RDF as WSF recorded highest WUE" [14].…”
Section: Nano Sensor With Drip In Crop Productionmentioning
confidence: 98%